Changes in principal component structure of countermovement jumps after a volleyball season - Kipp, K.; Kiely, M. T.; Geiser, C. F. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
The purpose of this study was to investigate changes in the principal component structure of countermovement jumps (CMJ) in female volleyball players over the course of a competitive season. Eleven NCAA Division I female volleyball players performed CMJs on a force plate before and after a competitive season. Discrete biomechanical variables were extracted from the force-time records of all CMJs and entered into a factor analysis. The analysis yielded two factors that could account for the biomechanical structure of the CMJs: a temporal and a force factor. Although no differences in factor scores were identified between pre- and post-season testing sessions, sub-group analysis highlighted large individual changes in temporal and force factor scores.